Does a Preschool Social and Emotional Learning Intervention Pay Off for Classroom Instruction and Children’s Behavior and Academic Skills? Evidence From the Foundations of Learning Project - Morris, Pamela (Early Educ Dev, 2013)
This article tests the hypothesis that children’s learning environment will improve through a social and emotional learning (SEL) intervention that provides preschool teachers with new skills to manage children’s disruptive behavior by reporting results from the Foundations of Learning (FOL) Demonstration, a place-randomized, experimental evaluation conducted by MDRC. Research Findings: Findings demonstrate that the FOL intervention improved teachers’ ability to address children’s behavior problems and to provide a positive emotional climate in their classrooms. Importantly, the FOL intervention also improved the number of minutes of instructional time, although the quality of teachers’ instruction was not improved. Finally, FOL benefited children’s observed behavior in classrooms, with lower levels of conflictual interactions and, at the trend level, higher levels of engagement in classrooms activities, relative to similar students randomly assigned to control classrooms. Practice or Policy: This study is one of an emerging body of research on the efficacy of SEL programs for preschool children living in poverty. Understanding the value-added of these programs (e.g., in increased instructional time and increased classroom engagement) as well as their limitations (e.g., in teachers’ instructional quality and children’s academic skills) will help us design the next set of more effective interventions for low-income children.